Who Decides When The Party Doesn’t? Authoritarian Voters and the Rise of Donald Trump - MacWilliams, Matthew C. (PS, political science & politics, 2016)
While the party decides theory explains the outcomes of past nomination battles for president, this year in the Republican presidential contest party insiders failed to anoint a standard bearer. Who decides when the party elites don’t? In 2016, it was America’s authoritarian voters. And their candidate of choice, Donald Trump, is anathema to party leaders. I argue that Trump’s rise is in part the result of authoritarian voters’ response to his unvarnished, us-versus-them rhetoric. The failure of Republican Party insiders to coalesce behind one candidate opened the door for Trump. Authoritarian-driven partisan polarization (Hetherington and Weiler 2009), increasing fear of real and imagined threats, and terrorist incidents abroad and at home provided the fuel for Trump’s campaign. And Trump’s message and manner ignited that fuel, propelling him to the Republican nomination for president.